The role of marketing and promotion management in assisting ICT incubatees in Malaysia - Abdul Khalid, Fararishah; Gilbert, David H.; Huq, Afreen; Ebrahim, Zuhriah (2013)
This paper examines the level of marketing and promotion management services available at ICT incubators and their impact on incubation performance. It argues that incubatees are more likely to perform when targeted marketing and promotion management services are provided in Malaysian ICT incubators. It adopts the mixed-methods approach to solicit the opinion of six incubator managers and 118 incubatees with regards to the availability of marketing and promotion management services at their respective incubators. This paper seeks to understand the impact of marketing and promotion management services on business incubation performance. It hypothesizes that integrating marketing and promotion management services in incubators impacts business incubation performance by transforming the level of services in these ICT incubators from first and second-generation incubators to third and fourth generation.